Analisis Nilai Perusahaan Sub Sektor Pertambangan Batu Bara yang Terdaftar di Bursa Efek Indonesia - Dhearista Adzhani; Rahman Amrullah Suwaidi (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study is to understand the effect of company growth and profitability on firm value with capital structure as a moderating variable in coal mining sub-sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research method is descriptive quantitative. The population in this analysis are 25 coal mining companies listed on the Indonesia Stock Exchange. The sampling technique chosen was by using a purposive sampling technique so that there were a sample of 22 companies that were in accordance with the established criteria. Analysis of the data used is Moderation Regression Analysis. The results showed, a) Company growth (AGR) has a positive influence on the company value (PBV), which is acceptable, the coefficient is 3.811 and Sig. 0.000 < = 0.05 the result is Significant (positive); b) Profitability (ROA) has a positive influence on Company Value (PBV) which is acceptable, the coefficient is 0.013 and Sig. 0.021 < = 0.05 the result is Significant (positive); c) Capital Structure (DER) moderating the effect of Firm Growth (AGR) on Firm Value (PBV) is unacceptable, the coefficient is 0.030 and Sig. 0.854 > = 0.05 the result is Non Significant (positive); d) Capital Structure (DER) moderating the effect of Profitability (ROA) on Firm Value (PBV) is unacceptable, the coefficient is -0.001 and Sig. 0.814 > = 0.05 the result is Non Significant (negative). In conclusion, company growth and profitability contribute to the value of Indonesian companies. Meanwhile, the capital structure cannot moderate the relationship between firm growth and profitability to firm value. Keywords: Firm Value, Company Growth, Profitability, Capital Structure